Bring history alive! : a sourcebook for teaching United States history \ - Ankeney, Kirk.; National Center for History in the Schools (U.S.) (Los Angeles, CA : National Center for History in the Schools, University of California, Los Angeles : Contact UCLA Book Zone, 1996)
A resource manual created by teachers and for teachers who wish to engage in an inquiry-based approach to historical knowledge and historical understanding.
"October 1996"--P. iv.
"Resource manual created by teachers and for teachers. It is presented for the consideration of those who wish to engage in an inquiry-based approach to historical knowledge and historical understanding."
Includes bibliographical references (p. 219-244).
Keywords: United States -- History -- Study and teaching